Case Report: Extensive Tumor Profiling in Primary Neuroendocrine Breast Cancer Cases as a Role Model for Personalized Treatment in Rare and Aggressive Cancer Types - Schaffrin-Nabe, Dörthe; Schuster, Stefan; Tannapfel, Andrea; Voigtmann, Rudolf (Frontiers in Medicine, 2022)
Neuroendocrine breast cancer (NEBC) is a rare entity accounting for <0.1% of all breast carcinomas and <0.1% of all neuroendocrine carcinomas. In most cases treatment strategies in NEBC are empirical in absence of prospective trial data on NEBC cohorts. Herein, we present two case reports diagnosed with anaplastic and small cell NEBC. After initial therapies failed, comprehensive tumor profiling was applied, leading to individualized treatment options for both patients. In both patients, targetable alterations of the PI3K/AKT/mTOR pathway were found, including a PIK3CA mutation itself and an STK11 mutation that negatively regulates the mTOR complex. The epicrisis of the two patients exemplifies how to manage rare and difficult to treat cancers and how new diagnostic tools contribute to medical management.